Banks' incentives and the quality of internal risk models - Matthew C. Plosser; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2014)
This paper investigates the incentives for banks to bias their internally generated risk estimates. We are able to estimate bank biases at the credit level by comparing bank-generated risk estimates within loan syndicates. The biases are positively correlated with measures of regulatory capital, even in the presence of bank fixed effects, consistent with an effort by low-capital banks to improve regulatory ratios. At the portfolio level, the difference in borrower probability of default is as large as 100 basis points, which can improve the typical loan portfolio's Tier 1 capital ratio by as much as 33 percent. Congruent with a regulatory motive, the sensitivity to capital is greater for larger, riskier, and more opaque credits. In addition, we find that low-capital banks' risk estimates have less explanatory power than those of high-capital banks with regard to the prices set on loans, indicating that low-capital banks not only have downward-biased risk estimates but that they also incorporate less information.
Keywords: G21; G28; 330; banks; incentives; default models; capital regulation; Basel II